Robot-Assisted Free Toe Pulp Transfer: Feasibility Study - Maire, Nicolas; Naito, Kiyohito; Lequint, Thierry; Facca, Sybille; Berner, Stacey; Liverneaux, Philippe (Journal of Reconstructive Microsurgery, 2012)
The current tendency of microsurgery is heading toward supermicrosurgery and microsurgery assisted by robotics. The aim of this work was to study the feasibility of a free hallux hemipulp transfer with a surgical robot in a cadaveric model. We used a human body. The intervention was realized by a Da Vinci SI® robot (Intuitive Surgical™, Sunnyvale, CA) in two stages: first taking off the medial hallux hemipulp, then transferring the hallux hemipulp to the radial thumb hemipulp. The intervention lasted 1 hour 59 minutes, exclusively with the Da Vinci SI® robot, without any interruption or outside intervention. Despite the absence of sensory feedback and an intervention 25% longer than in conventional microsurgery, we have demonstrated the feasibility of free hallux hemipulp transfer with a surgical robot. In the future, it is likely that the added benefits of the robot (physiological tremor suppression, user-friendly ergonomics, ultraprecise control of the instruments) will make the robot an indispensable tool for the surgeon.
Keywords: robot; flap; toe transfer